Macropropagation of macadamia nut (Macadamia integrifolia Maiden & Betche) through shoot cuttings - Arida Susilowati; Cut Rizlani Kholibrina; Mutya Kana Purba; Henti Hendalastuti Rachmat; Fifi Gus Dwiyanti; Ida Mallia Ginting (Talenta Publisher, 2025)
Macadamia integrifolia, locally known as Macadamia, is a tree species native toQueensland, Australia. The species is also recognized as an appropriate option forland rehabilitation in Indonesia, with one location being the Lake Toba catchmentarea in North Sumatra. This species is planted on a large scale because of itsadaptability and relatively short harvesting time. The high demand for macadamiaseeds cannot be supported by the species' ability to regenerate, as naturalregeneration is slow due to the thick and hard seed coat. As a result, a short-term,quality propagation technique that the community can easily use, such as shootcuttings, is required. This study aimed to determine the success of the shoot cuttingtechnique and the adventitious roots development on macadamia cuttings. Thecutting material was obtained from a healthy mother tree from the Sipiso-pisogarden, North Sumatra. The research was designed by using the factorial completeblock design with two factors randomized design with two factors namely cuttingmedia (A) and auxin application (B). The media treatment consisted of sand andtopsoil mixture (A1: 1/1 v/v), pure sand (A2), and pure topsoil (A3), while theauxin application consisted of 0 g (B1), 200 ppm (B2), and 600 ppm (B3). Alltreatments were carried out with 3 replications, each consisting of 5 individualcuttings. The results showed that macadamia shoot cuttings varied survival rateranging from 33.33 % to 86.66% with the rooting percentage ranging from 6.66%-40%. The highest survival rate was found in the top soil mixture: sand and withoutauxin treatment (88.66%) while the lowest was found in sand and without auxin(33.33 %). The cutting media and auxin application did not significantly affect allthe observed parameters. Based on histological root observations, the adventitiousroots of Macadamia form from the wound-induced root with a process that beginswith callus formation and ends with the advent of adventitious roots. This researchfound that the juvenile level of the cutting material used is considered a veryimportant factor in the success of macadamia shoot cuttings.